2009
DOI: 10.1158/0008-5472.can-09-0985
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Alterations in Tumor Stroma

Abstract: It was traditionally believed that the tumor was the seed that lay in the passive soil of the microenvironment, with the latter providing ''permissive elements'' for the tumor to grow and invade. Subsequently, it was recognized that both neoplasia and its microenvironment interacted as equal partners. Recent advances addressing genomic alterations in the tumor microenvironment, relevant to clinical outcome and treatment choices, are summarized. These include microenvironmental genomic alterations not only in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 39 publications
1
55
0
1
Order By: Relevance
“…On the other hand, the presence of somatic genetic alterations in active fibroblasts remains controversial (Campbell et al, 2009;Eng et al, 2009). While several groups reported the presence of mutations only in cancer epithelial cells, chromosomal loss of heterozygosity (LOH) and mutations have also been reported in CAFs by other groups (Campbell et al, 2011;Eng et al, 2009).…”
Section: Genetic and Epigenetic Changes In Breast Cancerassociated Mymentioning
confidence: 99%
“…On the other hand, the presence of somatic genetic alterations in active fibroblasts remains controversial (Campbell et al, 2009;Eng et al, 2009). While several groups reported the presence of mutations only in cancer epithelial cells, chromosomal loss of heterozygosity (LOH) and mutations have also been reported in CAFs by other groups (Campbell et al, 2011;Eng et al, 2009).…”
Section: Genetic and Epigenetic Changes In Breast Cancerassociated Mymentioning
confidence: 99%
“…[4][5][6][7] However, in recent years, genetic and epigenetic alterations have been also reported in stromal cells such as carcinoma-associated fibroblasts (CAFs) that may play a role in human carcinogenesis. 8,9 Carcinomas initiate and progress due to genetic and epigenetic alterations in epithelial cells. However, recently, these alterations have also been reported in stromal fibroblasts.…”
Section: Introductionmentioning
confidence: 99%
“…Despite certain genetic alterations found in stromal cells from various cancers (8), the absence of detectable genetic changes has been described in CAFs from breast and ovarian carcinomas, accompanied by dramatic changes in expression of genes encoding secreted or cell surface proteins (9,10). Despite their tumor-promoting function, it has been reported that CAFs generally lack cell-intrinsic oncogenic properties (11).…”
mentioning
confidence: 99%